Out of the Blue: Giving and receiving care: Aboriginal experiences of care-giving in the context of mental illness - Wright, Michael R (Curtin University, 2008)
This thesis is an exploration of the experiences of care-giving for Indigenous people living with a serious mental illness. The research included the experiences of those being cared for and those providing care. Due to past negative research experienced by Indigenous people, the study was conducted as a critical ethnography using multiple culturally appropriate methodologies and under the direction of a Study Reference Group. Participants were recruited through a person known to them, a culturally safe method of introduction. Thirteen in-depth case studies were conducted over 18 months, and participants' stories were constructed through multiple interviews, feedback and workshop sessions. Findings included the identification of a serious disconnection between mental health providers and Indigenous Australian families living with serious mental health issues. This disconnection was due to mental health providers lacking understanding of Indigenous needs and of the complexity and concepts of Indigenous care-giving. One outcome from this study was the proposal of an Indigenous care-giving model. The key elements of an Indigenous model of care-giving are the importance of relationships and reciprocity in holding and sustaining culture, and the significance of cultural responsibility. When mental health providers lack understanding of these attributes it has serious implications for their interactions with Indigenous people. This thesis offers recommendations for future research and for improved standards for mental health care provision.